Pendidikan dan Emansipasi wanita dalam Pandangan Abbas Mahmud al-’Aqqad (Nadlariyah Abbas Mahmud 'Aqqad fi Tarbiyatil Mar'ati wa Tahririha) - Nur Sa'idah (Faculty of Tarbiyah and Education State Islamic University (UIN) Sunan Kalijaga Yogyakarta, Indonesia, 2014)
The issue of women is still a serious discourse for discussion, both about the identity, The issue of women is still a serious discourse for discussion, both about the identity, position, and role, even to the character and intellect. This article discusses the theory of education and emancipation of women in view of Abbas Mahmud al - 'Aqqad, an Egyptian thinker, poet, philosopher, and journalist scholars in the late - 19th and early 20th century. According to al - 'Aqqad, women have equal footing with men in education and all social roles. But the natural differences between women and men demanding the division of different roles, so that the relationship between women and men should be a partnership. Conservative views of ' Aqqad theory based on the Koran, the Hadith position, and role, even to the character and intellect. This article discusses the theory of education and emancipation of women in view of Abbas Mahmud al-‘Aqqad, an Egyptian thinker, poet, philosopher, and journalist scholars in the late - 19th and early 20th century. According to Him, women have equal footing with men in education and all social roles. But the natural differences between women and men demanding the division of different roles, so that the relationship between women and men should be a partnership. Conservative views of ‘ Aqqad theory based on the Koran, the Hadith, and the research on the female characters. This theory is in line with the structuralist functionalist theory. Structuralist theory gravitates to sociology while learning functionalist psychological theory, but they have the same conclusion, that the relationship between women and men is the preservation of harmony, not competition. ‘Aqqad’theory could be a solution to the issue of family crisis and child neglect that often occurs as a result of the division of the marital partnership roles are less than ideal. and research on the female characters. 'Aqqad’s theory could be a solution to the issue of family crisis and child neglect that often occurs as a result of the division of the marital partnership roles are less than ideal.